A moral resilience intervention to decrease moral injury severity: an 'ABA' single subject design with a rural woman veteran. - McDaniel, Justin T.; Ezigbo, Ugochukwu; Copeland, Lt. Col. Ret. Paul (Journal of Religion & Spirituality in Social Work)
Although moral injury is commonly reported by military veterans, the social work literature lacks evidence for efficacious treatments that social workers can administer remotely and thus serve the nearly 25% of veterans who live in resource-deprived rural areas. The purpose of the present study was to test a self-administered, interactive, online moral injury resilience intervention grounded in forgiveness theory, called BREACH/PREACH, in an "ABA" single subject study design with a rural-dwelling woman veteran. The primary target in this study was a moral injury severity rating as measured by the behavioral economics-inspired "Moral Injury Purchase Task" (MIPT) during a seven-day baseline period, a 12-day intervention period, and a seven-day follow-up period. Four behavioral economic demand indices derived from the MIPT (i.e. intensity, Pmax, Omax, and breakpoint) decreased from the baseline period to the intervention period (Tukey HSD p's < 0.05) and from the intervention period to the follow-up period (Tukey HSD p's < 0.05). Although limitations accompany single subject study designs, this project provides preliminary evidence of the efficacy of remote moral injury resilience intervention that social workers could prescribe to reduce moral injury severity in rural-dwelling military veterans.